The Southern Train Passengers’ Expectation and Perception toward the Quality Service of the State Railway of Thailand - Junkaew, Siriwan (JOURNAL OF SOUTHERN TECHNOLOGY, 2021)
The objective of this research related to the service quality of the Southern Line of the State Railway of Thailand are to: (1) study the level of passengers’ expectation and perception (2) compare the passengers’ expectation and the perception. The population of this research was the 400 southern line passengers who traveled by the second class cabin. The researcher compiled and analyzed the data in terms of frequency, percentage, mean, and t-tested. The result showed that all aspects as well as specifics of the passengers’ expectation and perception were at the high level and medium level, respectively. The highest level of passengers’ expectation and perception were responsiveness and reliability, respectively. Comparison between passengers’ expectations and perceptions in terms of tangibles, empathy, assurance, responsiveness and reliability were statistically significant differences.